Impacts of Export Restrictions on the Global Personal Protective Equipment Trade Network During COVID‐19. Issue 4 (7th December 2021) - Ye, Yang; Zhang, Qingpeng; Cao, Zhidong; Chen, Frank Youhua; Yan, Houmin; Stanley, H. Eugene; Zeng, Daniel Dajun
Abstract: The COVID‐19 pandemic has caused a dramatic surge in demand for personal protective equipment (PPE) worldwide. Many countries have imposed export restrictions on PPE to ensure the sufficient domestic supply. The surging demand and export restrictions cause shortage contagions on the global PPE trade network. Here, an integrated network model is developed, which integrates a metapopulation model and a threshold model, to investigate the shortage contagion patterns. The metapopulation model captures disease contagion across countries. The threshold model captures the shortage contagion on the global PPE trade network. Due to the Pareto distribution in global exports, the shortage contagion pattern is mainly determined by the export restriction policies of the top exporters. Export restrictions exacerbate the shortages of PPE and cause the shortage contagion to transmit even faster than the disease contagion. To some extent, export restrictions can provide benefits for self‐sufficient countries, at the sacrifice of immediate economic shocks at not‐self‐sufficient countries. With export restrictions, a large amount of PPE is hoarded instead of being distributed to where it is most needed, particularly at the early stage. Cooperation between countries plays an essential role in preventing global shortages of PPE regardless of the production level. Except for promoting global cooperation, governments and international organizations should take actions to reduce supply chain barriers and work together to increase global PPE production. Abstract : An integrated network model is proposed to characterize the COVID‐19 contagion and personal protective equipment (PPE) shortage contagion patterns worldwide. Extensive simulations reveal that export restrictions exacerbate the shortages of PPE and cause fast shortage contagion that transmits faster than the disease contagion. Results also indicate that international cooperation plays an essential role in preventing global shortages of PPE.